Pengaruh Kompetensi Pengelola, Keefektifan Pengendalian Internal dan Kesesuaian Kompensasi Terhadap Kecenderungan Kecurangan Akuntansi Dalam Pengelolaan Dana Bumdes - Sudariani, Ni Made Rina; Yudantara, I Gede Agus Pertama (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2021)
BUMDes is a form of village empowerment built by village officials with the aim of realizing village autonomy and being able to increase village original income. This research was conducted in order to obtain empirical data regarding the influence of manager competence, effectiveness of internal controls and suitability of compensation on the tendency of accounting fraud in the management of BUMDes funds in Buleleng Regency. This research is a quantitative research, sourced from questionnaire data and measurement using a 4 point Likert scale. The population in this research were all BUMDes heads and treasurers in Buleleng Regency with a total of 224 administrators. The sample selection technique used in this research was purposive sampling, with a total of 78 samples of BUMDes administrators. The sample selection consideration is BUMDes which has total assets of IDR 1 billion and is formed by the Mandiri Sadhu Gate (GSM). The results of this study state that the manager's competence (X1), the effectiveness of internal control (X2) and the suitability of compensation (X3) each have a negative and significant effect on the tendency of accounting fraud.Â